The Relationship Between NH3 And NO2 Content and Bacterial Abundance Vibrio on Media Cultivation Shrimp Vaname (Litopenaeus vannamei) - Toto Hardianto; Aulia Magfirah Ilham Perdana; Yunarty Yunarty; Siti Aisyah Saridu; Feby Triadi (Journal La Lifesci, 2025)
Indonesia, as an archipelagic country, holds great potential in marine and fisheries resources. Whiteleg shrimp (Litopenaeus vannamei) is one of the most economically valuable aquaculture commodities, with production reaching 5,812.2 thousand tons in 2020, an increase of 52.8% compared to 2015. However, disease outbreaks remain a major challenge in shrimp farming. One common disease is vibriosis, caused by Vibrio sp., an opportunistic, highly virulent, Gram-negative and facultative anaerobic bacterium. Therefore, early detection of Vibrio abundance is essential for prevention and control efforts. This Final Internship Project (KPA), titled “Abundance of Vibrio Bacteria in Whiteleg Shrimp Culture Media,” aimed to determine the abundance of Vibrio sp. in shrimp ponds and analyze the influence of water quality parameters (NH₃, NO₂, and plankton). The internship was conducted from February 6 to April 17, 2025, at PT Parigi Aquakultura Prima, Central Sulawesi. Activities included water sampling, NH₃ and NO₂ testing, plankton density measurement, sterilization, TCBS media preparation, bacterial inoculation, and enumeration. Observations were carried out in six pond plots with weekly sampling from Day of Culture (DOC) 9 to 79. The regression model obtained was Y = 164.808 + 153.951X₁ + 2092.103X₂ + 0.000X₃, indicating that increasing NH₃ and NO₂ levels positively contribute to Vibrio abundance, each raising bacterial numbers by 153,951 and 2,092,103 units per one-unit increase, respectively. Plankton showed no significant effect. Thus, NH₃, NO₂, and plankton have partial influence on Vibrio abundance, although plankton contributes minimally.